Study of Various Clinical Presentations, Laboratory Parameters and Echocardiographic Findings in Newly Diagnosed Hypertensive Patients - Hetal, Chauhan; Kruti, Rajvansh; Hiren, Pandya (Indian Journal of Pharmacy Practice)
Objective: To study various clinical presentations, laboratory parameters, electrocardiographic and echocardiographic findings in newly diagnosed hypertensive patients. Methods: This study included 100 cases of newly diagnosed hypertension. The target population involved all adults presented with first time hypertension as indoor as well as outdoor patients of age > 18 years in both male and female according to JNC 8 guideline.(Systolic blood pressure >140; Diastolic Blood Pressure >90). Results: Incidence of hypertension was found higher among the 61-70 years age group and least among 18-30 age group. Incidence was higher in male (62%) patients than female (38%) patients. Addiction like tobacco/biddi/chhikani/alcohol, dyslipidemia, positive history of CVD and obesity were associated risk factors seen in 44%, 44%, 30% and 16% respectively. Commonest symptom was Headache (25%), followed by chest pain (21%). Total mean systolic and diastolic blood pressure was ( 175/100 mmHg). Among all newly diagnosed hypertension patients, abnormal triglyceride, total cholesterol, LDL, HDL, Urine R/M and serum creatinine were present in 44%, 40%, 38%, 36%, 17% and 5% patients respectively. The most common finding in ECG was LV Strain (42%), followed by LVH (30%).Commonest finding in 2D ECHO was concentric LVH (64%). 14% patients had retinopathy at the time of diagnosis of hypertension. Conclusion: Development of hypertension is depended on multiple risk factors like age, sex, decreased physical activity, obesity, various addiction and hormonal changes. Identifying the risk factors helps in further management and prevention of complications of hypertension.
Keywords: Hypertension; Adults; Newly diagnosed; Electrocardiographic; Echocardiographic